ELLIPTICAL TIME IN AÑO SABÁTICO (2000) BY JOSÉ GÜICH - Honores, Elton (2021)
In this work we will analyze Año sabático (2000) "opera prima" by the Peruvian writer José Güich Rodríguez, based on the category of time that underlies the texts of the book. We will lean on our theoretical proposal presented in Fantasmas del futuro (2018) to establish the singularities of the use of time in Güich's texts, as well as its link to genres such as science fiction and fantasy. We finally discovered his poetry about the fiction included in one of his stories.